Role of Greenland Freshwater Anomaly in the Recent Freshening of the Subpolar North Atlantic. Issue 5 (25th May 2019) - Dukhovskoy, D. S.; Yashayaev, I.; Proshutinsky, A.; Bamber, J. L.; Bashmachnikov, I. L.; Chassignet, E. P.; Lee, C. M.; Tedstone, A. J.
Abstract: The cumulative Greenland freshwater flux anomaly has exceeded 5, 000 km 3 since the 1990s. The volume of this surplus freshwater is expected to cause substantial freshening in the North Atlantic. Analysis of hydrographic observations in the subpolar seas reveals freshening signals in the 2010s. The sources of this freshening are yet to be determined. In this study, the relationship between the surplus Greenland freshwater flux and this freshening is tested by analyzing the propagation of the Greenland freshwater anomaly and its impact on salinity in the subpolar North Atlantic based on observational data and numerical experiments with and without the Greenland runoff. A passive tracer is continuously released during the simulations at freshwater sources along the coast of Greenland to track the Greenland freshwater anomaly. Tracer budget analysis shows that 44% of the volume of the Greenland freshwater anomaly is retained in the subpolar North Atlantic by the end of the simulation. This volume is sufficient to cause strong freshening in the subpolar seas if it stays in the upper 50–100 m. However, in the model the anomaly is mixed down to several hundred meters of the water column resulting in smaller magnitudes of freshening compared to the observations. Therefore, the simulations suggest that the accelerated Greenland melting would not be sufficient to cause the observed freshening in the subpolar seas and other sources of freshwater have contributed to the freshening. Impacts on salinity in the subpolar seas of the freshwater transport through Fram Strait and precipitation are discussed. Plain Language Summary: Accelerated Greenland ice sheet loss has contributed about 5, 000 km 3 of freshwater into the subpolar North Atlantic since 1993, which is half of the freshwater volume propagating across the North Atlantic with the Great Salinity Anomaly in the 1970s. The volume of the Greenland freshwater anomaly is expected to cause substantial freshening in the North Atlantic and impact the Arctic and subarctic climate. Analysis of hydrographic observations identifies freshening signals in the subpolar seas in the 2010s possibly related to the increased Greenland freshwater flux. In order to verify this relationship, numerical experiments with passive tracers released at freshwater sources along the coast of Greenland are employed to track propagation, mixing, and accumulation of the Greenland freshwater flux anomaly. The model experiments demonstrate that a substantial volume of the Greenland freshwater anomaly is retained in the subpolar North Atlantic but is mostly mixed in the upper 500 m of the water column resulting in smaller magnitudes of the freshening signal compared to the observations. Thus, the simulations suggest that the accelerated Greenland melting would not be sufficient to cause the observed freshening in the subpolar seas and other sources of freshwater have contributed to the freshening. Key Points: Freshening propagating eastward across the subpolar North Atlantic in the 2010s followed the salinity increase observed since the mid‐1990s Simulated content of Greenland freshwater anomaly is high in the western part and low in the Nordic Seas in agreement with observations Greenland freshwater anomaly is vertically mixed, leading to small‐salinity decrease suggesting contribution from other freshwater sources